Descripción de los conodontos del Givetiense y Frasniense - Liao, Jau-Chyn; Valenzuela-ríos, José Ignacio; Rodríguez, Sergio (Coloquios de Paleontología, 2001)
A Givetian and Early Frasnian conodont sequence from Renanué section is presented. As a result, 28 taxa belonging to Polygnathus, Icriodus, Skeletognathus and Klapperina are described. 21 taxa are described and illustrated for the first time from Renanué section. This conodont succession will allow a very fine biostratigraphical subdivision of the studied interval.
Keywords: Systematic; Conodonts; Givetian; Frasnian; Renanué; Aragonian Pyrenees